STATUS TAKSONOMI FAUNA DI INDONESIA DENGAN TINJAUAN KHUSUS PADA COLLEMBOLA - Yayuk R. - Suhardjono (ZOO INDONESIA, 2006)
Suhardjono, Y. R. 2006. Status of Indonesian fauna taxonomy with specialreference on collembola. Zoo Indonesia Vol. 15 (2): 67-86. Taxonomy is a sciencethat covers characterization, classification and naming of any living things. InIndonesia, mostly the taxonomy works are not recognized proportionally. Peoplethough it is only a matter of identifying, classifying and followed by remembering theLatin name. This wrong perception has caused the lack of development on thetaxonomy aspects in Indonesia. Data revealed that the Indonesian taxonomist numberis very low, and so does with the publication products. This situation is contradictedwith the wealth status of Indonesia on the biodiversity. Communication among the taxaspecialist is one key factor for the development of taxonomy science, from wheresome collaborative works through exploration or publications can be developed.